2022
DOI: 10.1177/23328584211071115
|View full text |Cite
|
Sign up to set email alerts
|

School Absenteeism and Academic Achievement: Does the Reason for Absence Matter?

Abstract: Studies consistently show associations between school absences and academic achievement. However, questions remain about whether this link depends on the reason for children’s absence. Using a sample of the Scottish Longitudinal Study (n = 4,419), we investigated whether the association between school absenteeism and achievement in high-stakes exams at the end of compulsory and postcompulsory schooling varies with the reason for absence. In line with previous research, our findings show that overall absences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…In this regard, teachers should question their own educational practice and develop a close relationship with students by considering their worries and interests. Moreover, teachers should promote positive relationships between learners by implementing cooperative learning strategies that foster students' inclusion and academic achievement (Filippello et al, 2019;Klein et al, 2022;Wattanawongwan et al, 2021). All adolescents would benefit from these actions, but especially those with High SRB, who would perceive high school as a motivating environment for learning.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, teachers should question their own educational practice and develop a close relationship with students by considering their worries and interests. Moreover, teachers should promote positive relationships between learners by implementing cooperative learning strategies that foster students' inclusion and academic achievement (Filippello et al, 2019;Klein et al, 2022;Wattanawongwan et al, 2021). All adolescents would benefit from these actions, but especially those with High SRB, who would perceive high school as a motivating environment for learning.…”
Section: Discussionmentioning
confidence: 99%
“…For England, an increase of overall absence levels decreased achievement at the end of primary and compulsory secondary education (Department for Education, 2016). A recent Scottish study reported that school absences in secondary school have a negative impact on adolescents' achievement in high-stakes national exams at the end of compulsory and post-compulsory schooling (Klein et al, 2022).…”
Section: Consequences Of School Absenteeismmentioning
confidence: 99%
“…School absenteeism is a pervasive problem and has detrimental consequences for children's school achievement (e.g., Department for Education, 2016; Klein et al, 2022). This is because children miss out on teacher-led lessons, peer interactions, and the development of positive psychosocial (e.g., prosocial behaviour) or aspirational dispositions (e.g., educational aspirations and motivation) that may stimulate their learning and development (Kirksey, 2019;Morrissey et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Martin et al (2020) found that school officials often pejoratively viewed vulnerable absentee students as truant rather than pursue a more accurate mental health-based conceptualization and remediation process. This applies to 10.3389/feduc.2022.977672 the use of the term "unexcused absences" as well, which can erroneously and disparagingly signal deviance and which is not always indicative of student achievement problems (Donat et al, 2018;Klein et al, 2022). Unexcused absences also tend to be disproportionately and unfairly assigned to vulnerable student groups (McNeely et al, 2021).…”
Section: Subtyping School Attendance Problems Historical Categoriesmentioning
confidence: 99%
“…School attendance and school attendance problems have been a focus of research, health-based clinical work, and educational and social policy for over a century (e.g., Kline, 1897;Klein et al, 2022). Such extended historical focus is due in part to the fact that school attendance is associated with myriad positive effects 10.…”
Section: Introductionmentioning
confidence: 99%